Evaluasi Niatan Perilaku Pengguna Wanita pada Touch Point Platform Kecantikan Female Daily Menggunakan Theory Of Planned Behavior Termodifikasi - Dimitri Yola Naluritha; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Female Daily is a discussion platform dedicated for women which contain collection of information and articles that provide website and mobile applications as touch points to users. To maintain user intention from their behavior, an evaluation of users who have accounts on the touch point platform using a Theory of Planned Behavior modified (DTPB) were evaluated. with Relative advantages, Compatibility, Complexity, Attitude, Normative Influences, Subjective Norms, Facilitating Conditions, Perceived Behavioral Control, Curiosity, Self-efficacy, Perceived Enjoyment and Intention. This research used descriptive analysis and instrument formed as questionnaire with a study population of 189,000 Female Daily active users. Calculation of sample used Slovin formula with error rate 10% generated 122 people as participants. Mean results showed variables Perceived Behavioral Control (4,15), Facilitating Conditions (3,8), Self Efficacy (4,1), Subjective Norm (3,46), Normative Influence (3,38), Attitude (4,45), Relative Advantages (4,64), Compatibility (4,44), Complexity (1,97), Curiosity (4,53), Perceived Enjoyment (4,48) and Intention (3,38). Recommendations formed such as maintain and enhance up-to-date information on the existing touch points, adjust a simple layout display and based on user needs, introduction of a wider platform through advertising promotion on social media and beauty influencers, increasing convenience among users with enhanced features report account that violates the rules.